Numerical simulation study on the evolution of wrinkling defects in carbon fiber laminates based on spatial decomposition damage variable method - ZHENG Haocheng; ZHOU Bo; LI Hui; WANG Yajie; SUN Ning; ZHANG Xueyan (Jixie qiangdu)
In order to investigate the compression damage evolution of carbon fiber laminates with wrinkles and accurately predict the mechanical behavior of damage initiation and propagation, a progressive damage finite element model was proposed based on three-dimensional elastic theory by employing a spatial decomposition of damage variables method to establish the damage constitutive relation. Firstly, the maximum stress and Puck failure criteria were used to predict the intralaminar damage initiation, and the damage variables were calculated in combination with the mixed-mode damage evolution law. Secondly, based on the physical meaning of the damage variables, a spatial decomposition was carried out in the fracture plane coordinate system, and the damage constitutive relation was derived by substituting the damage stiffness matrix. Then in order to predict the interlaminar stress state and damage behavior of laminates, a cohesive zone model with a bilinear traction-separation law was adopted. Finally the corresponding Vumat subroutine was developed and implemented in Abaqus software for the numerical simulation analysis of quasi-static compression loading at 0.25 mm/min.The stress-displacement curves and damage distribution of laminates predicted by the finite element model are in good agreement with test results. The proposed calculation method is simple and direct for determining true stress, making it convenient for analyzing and identifying the damage location and damage evolution of composite laminates with wrinkles.